Molecular characterisation of SMARCB1 and NF2 in familial and sporadic schwannomatosis. Issue 6 (19th February 2008) - Hadfield, K D; Newman, W G; Bowers, N L; Wallace, A; Bolger, C; Colley, A; McCann, E; Trump, D; Prescott, T; Evans, D G R
Abstract : Background: Schwannomatosis is a rare condition characterised by multiple schwannomas and lack of involvement of the vestibular nerve. A recent report identified bi-allelic mutations in the SMARCB1/INI1 gene in a single family with schwannomatosis. We aimed to establish the contribution of the SMARCB1 and the NF2 genes to sporadic and familial schwannomatosis in our cohort. Methods: We performed DNA sequence and dosage analysis of SMARCB1 and NF2 in 28 sporadic cases and 15 families with schwannomatosis. Results: We identified germline mutations in SMARCB1 in 5 of 15 (33.3%) families with schwannomatosis and 2 of 28 (7.1%) individuals with sporadic schwannomatosis. In all individuals with a germline mutation in SMARCB1 in whom tumour tissue was available, we detected a second hit with loss of SMARCB1 . In addition, in all affected individuals with SMARCB1 mutations and available tumour tissue, we detected bi-allelic somatic inactivation of the NF2 gene. SMARCB1 mutations were associated with a higher number of spinal tumours in patients with a positive family history (p = 0.004). Conclusion: In contrast to the recent report where no NF2 mutations were identified in a schwannomatosis family with SMARCB1 mutations, in our cohort, a four hit model with mutations in both SMARCB1 and NF2 define a subset of patients with schwannomatosis.